Clinician preference and comparison of the efficacy of ondansetron, granisetron, and palonosetron in preventing chemotherapy-induced nausea and vomiting among children receiving moderate or highly emetogenic chemotherapy - Rohan Bansal; Sonam Agrawal; Saurabh Kohli; Kunal Das (Elsevier, 2023)
Background: Chemotherapy-induced nausea and vomiting (CINV) is a common and significant problem in children receiving chemotherapy. While 5-HT3 blockers are commonly used antiemetics, there is no consensus about choice among them. This study was planned to look for clinician preference for 5-HT3 blocker agent, clinical efficacy, and need for rescue medicines. Material and methods: The prospective, observational study was conducted in a tertiary care cancer center in Uttarakhand in patients aged 1-18 years. Patients received one of the three 5-HT3 blockers, ondansetron, palonosetron, or granisetron, according to the choice of treating clinician in each chemotherapy cycle. Observations were made for breakthrough CINV, retching episodes, and the need for rescue medication. The assessment was done by the patient and attendants on a self-reporting scale and by the nursing staff based on CTCAE (ver 4.03) criteria. Results: Ondansetron was the most commonly used 5-HT3 blocker; used in 53% of the chemotherapy cycles. All three 5-HT3 blockers evaluated in this study, showed efficacy in preventing acute CINV. However, granisetron was inferior based on the self-reporting scale. The nursing assessment showed better control of acute CINV with palonosetron in terms of grade and number of breakthrough CINV episodes (p < 0.005). All three groups showed a similar need for rescue medications. The mean requirement of rescue medication was comparable across the cohorts receiving 3 different 5-HT3 blockers as CINV-prophylaxis for moderate or high emetogenic chemotherapy. Conclusion: All three 5-HT3 blockers compared in this study had good efficacy in preventing acute CINV. Palonosetron was better in controlling acute CINV as per nursing assessment.